Adult prostatic sarcoma: A contemporary multicenter Rare Cancer Network study. Issue 10 (8th June 2017) - De Bari, Berardino; Stish, Bradley; Ball, Mark Wayne; Habboush, Yacob; Sargos, Paul; Krengli, Marco; Bossi, Alberto; Stabile, Armando; Sole Pesutic, Claudio; Lestrade, Laëtitia; Smeenk, Robert Jan; Jereczek‐Fossa, Barbara Alicja; et al.
Abstract : Introduction: Adult prostatic sarcoma (PS) is a rare disease. While surgery is considered the standard approach, the role of other therapies is not completely established. We report results of the largest multicentric contemporary cohort of PS patients. Materials and Methods: This study included 61 adult PS patients treated in 16 American and European Institutions. Median age was 64.4 years (range: 22‐87). Curative surgery was delivered in 48 patients (prostatectomy = 26, cystoprostatectomy = 22), usually with lymphadenectomy ( n  = 40). Curative radiotherapy (RT) was delivered in 32 patients, as radical ( n  = 5), neoadjuvant ( n  = 10), or postoperative treatment ( n  = 17). Eighteen patients received chemotherapy. None of the patients received hormonal therapy. Results: Median follow‐up was 72 months (95%CI: 55‐not reached). Five‐year local control (LC), overall survival (OS), cancer‐specific survival, disease‐free survival, and metastases‐free rates were 47%, 53%, 56%, 35%, and 35%, respectively. Notably, curative RT (neoadjuvant, adjuvant, or definitive) was associated with improved 5‐year LC (55% vs. 31%, P  = 0.02) and OS (59% vs. 46%, P  = 0.1). Surgically treated patients presenting with a cT3‐4 tumor ( n  = 31), who received RT ( n  = 24), had a significantly improved 5‐year LC (68% vs, 33%, P  = 0.004) and OS (65% vs. 21%, P  < 0.001) rates compared to patients not receiving RT. cT4 patients demonstrated a significantly lower 5‐year OS (43% vs. 61%, P  = 0.006) and LC (29% vs. 69%, P  < 0.001) rates. Histologic subtype was not associated with LC and OS, but patients with prostatic stromal sarcoma, rhabdomyosarcoma, or sarcomatoid carcinoma had worse 5‐year LC compared to other types (47% vs. 55%) and OS (49% vs. 58%). Conclusion: Adult PS has a poor prognosis. Locally advanced tumors have poor LC and OS rates. Curative RT should be considered part of the multidisciplinary approach to PS.